Cyclic Loading Responses of Cement-Stabilised Base Materials: An investigation on moduli for pavement design - Nusit, K.; Jitsangiam, Peerapong; Kodikara, J.; Bui, H. (New Zealand Geotechnical Society, 2015)
In the general Mechanistic-Empirical pavement design guideline, the design parameter normally used in representing the response of stabilised pavement material is the elastic modulus measured from a statically-monotonic compression test. Nevertheless, this elastic modulus may not respond to actual behaviour of real pavement which is subjected to cyclic loading from moving vehicles. Using the elastic modulus in pavement analysis could lead to an inaccurate estimation of the stress-strain relationship which is relevant to a pavement response prediction under traffic loading conditions. In this research, the dynamic modulus of cement-stabilised material measured from Asphalt Mixture Performance Tester was examined to be used as a pavement design parameter with consideration of cyclic (traffic) loading conditions. The laboratory results from this research reveal that the cyclic response of cement-stabilised material in term of the dynamic modulus is not much affected by a variation on temperatures and loading frequencies.However, the dynamic modulus is greatly influenced by cement contents and curing periods. Moreover, the elastic moduli measured based on different strain rates was also examined. In order to compare the effects of modulus to the pavement response, finite element analysis was performed in this research by altering the modulus of base course layer. Flexural modulus of cement-stabilised base material determined by Chummuneerat et al. (2013) was also included in the finite element analysis. The results of the finite element analysis show that a tensile strain at a critical location can be reduced by 20% if the elastic modulus of a base course layer were replaced by the dynamic modulus and the flexural modulus. In addition, stress induced by the traffic load can be evenly transferred to the subgrade layer by applying the dynamic modulus and the flexural modulus in the analysis.